The effects of biochar application method on soil properties and plant growth performance / Muhamad Fadhli Mohd Asri - Mohd Asri, Muhamad Fadhli (Faculty of Plantation and Agrotechnology, 2019)
The glasshouse study was conducted to determine the effect of biochar application method on soil properties and plant growth by using biochar derived from empty fruit bunch (EFB). There was four treatments of application method incorporated biochar and soil such as treatment (T1) control soil only, treatment (T2) biochar in side soil, treatment (T3) biochar in broadcast soil and Treatment (T4) incorporated or mixture biochar and soil. The main objective is evaluated the effect of biochar application on soil properties and plant growth performance. The result showed that incorporated biochar and soil was the best method application biochar. Treatment incorporated biochar and soil has significant effect on the plant height, chlorophyll content and soil properties as compared to other treatments.